Why are older adults victims of fraud? Current knowledge and prospects regarding older adults' vulnerability to fraud. Issue 3 (27th May 2019) - Shao, Jingjin; Zhang, Qianhan; Ren, Yining; Li, Xiying; Lin, Tian
ABSTRACT: Older adults are disproportionately targeted by various kinds of fraud, which result in irreversible economic losses and great psychological distress. Over the past years, researchers have conducted systematic research on the prevalence, under-reporting, and research methods of fraud victimization in older adults. Research paradigms regarding fraud victimization among older adults have mainly included cognitive, emotion regulation and motivation, and comprehensive paradigms. Factors shown to influence fraud victimization among older adults include cognitive decline, emotional regulation and motivational changes, their overly trusting nature, psychological vulnerability, social isolation, risk-taking, and a lack of knowledge and information regarding fraud prevention. Based on a review of the literature, future research can benefit from constructing a comprehensive fraud victimization theory, improving research methods, extending existing research, exploring physiological mechanisms of elderly fraud, and strengthening prevention and intervention efforts.